GURU DI ERA ALGORITMA: KAJIAN PUSTAKA SISTEMATIS ATAS TRANSFORMASI PERAN PENDIDIK, PERSONALISASI PEMBELAJARAN BERBASIS AI, DAN TANTANGAN ETIKA TEKNOLOGI DALAM PENDIDIKAN INDONESIA - Busnawir; Abdul Wahab Syakhrani; Elmiwati (CV. Lafadz Jaya, 2026)
The integration of artificial intelligence (AI) into education has triggered a fundamental transformation of the role of educators, learning paradigms, and the technological ethics landscape in Indonesia. This study employs a literature review to understand the dynamics of the transformation of the teacher’s role, the potential of AI-based personalised learning, and the accompanying ethical challenges within the context of Indonesian education. The findings reveal that the role of the teacher has evolved from a transmitter of knowledge to a learning designer, data-informed mentor, and ethical gatekeeper who orchestrates the synergy between human capacity and algorithmic systems. AI-based personalised learning demonstrates significant effectiveness in enhancing student learning outcomes, motivation, and autonomy through real-time diagnostic mechanisms, automatic curriculum adaptation, and intelligent content curation. However, the implementation of AI in education faces complex ethical challenges, including breaches of student data privacy, algorithmic bias that reinforces structural inequalities, a lack of algorithmic transparency, and the risk of over-reliance that erodes human cognitive capacity. This study recommends the development of a teacher competency framework integrating AI literacy and technology ethics, the strengthening of educational data protection regulations, the implementation of independent algorithmic audit mechanisms, and the adoption of human-centred design principles in the development of educational technology. The transformation of Indonesian education in the algorithmic era requires a collective commitment to building a harmonious, fair, and sustainable learning ecosystem, where AI functions as an empowering tool that reinforces, rather than replaces, the humanistic values of education.